Legal Due To The Transfer of Rights to Agricultural Land to Non Agriculture In The City of Tasikmalaya - Ami Nurjannah (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
In this study, the researcher uses the title Legal Strength and Authentic Deed Agricultural land is one of the ecosystem supporting the life of Indonesian citizen, fertile land into fruit that will produce food resources for all residents who are in the vicinity. In order to maintain food resources in Indonesia farmers must do the care and protection of plants that they plant whether rice, corn, or other plants that produce agricultural fruits. Good resources are resources that are continually given attention and management periodically to achieve perfect results in supplementary. In addition to the care of the farmers to realize an increasingly advanced ecosystem need the Government's efforts in supporting the advancement of food resources, because so the empowerment of nature and governance of each other is aligned and balanced, but it is not easy in the implementation necessary to build awareness to make it happen. Entering a new era as now the government is doing many changes and shifts on the basis to make it a source of income in a different field, as well as the transition of agricultural land function into a building or other building materials to achieve a faster outcome and the Kerab is considered more appropriate and luxurious. The transition of agricultural land is no longer a taboo in life as it is today, to advance the technology and development of a region or country of agriculture has become a major target of entrepreneurs and governments engaged in the field. The farmland turned into a building is a question of how validity is in the process of implementation. Because with the transition the land can affect the sustainability of the lives of the inhabitants and farmers around it. Because the manifestation of a seumber of natural power is to defend and develop it to keep it going.